The course of the professional development and the level of job satisfaction among physiotherapists - Jaros, Agata A. (Medical Studies/Studia Medyczne, 2015)
Introduction: The occupation of a physiotherapist, due to its nature, is very challenging. It requires continuous work on oneself and the improvement of professional skills. Aim of the research : To assess the level of competence, professional development, and job satisfaction among a group of active physiotherapists. Material and methods : The study involved a group of 62 physiotherapists, among whom a questionnaire was conducted. The survey contained questions concerning demographic data of the respondents, general working conditions, and satisfaction with their profession. The calculations and graphs presented in the descriptive statistics, as well as the statistical hypotheses, were all performed in MS Excel’s spread sheet and T-Czuprow’s similarity rate. Results: The results show the high activity concerning participation in specialised courses in physiotherapy methods and the use of specialised literature. The level of job satisfaction is high, at about 70%, in all groups. The character of the work and positive relations with co-workers and supervisors were assessed highest and salary and promotion opportunities lowest from all the determinants of job satisfaction. Although the level of job satisfaction itself is acceptable, nearly 1/3 of respondents have no plans for further development and 40% do not plan to follow this profession in the future. Conclusions : After graduation they often willingly improve their professional qualifications. The level of job satisfaction itself is acceptable; however, the lack of plans for further development or willingness to follow this profession in the future can cause a significant decline in the number of professionally active physiotherapists.